β Subunits Control the Effects of Human Kv4.3 Potassium Channel Phosphorylation - Abbott, Geoffrey W. (Frontiers in Physiology, 2017)
The transient outward K+ current, Ito, activates early in the cardiac myocyte action potential, to begin repolarization. Human Ito is generated primarily by two Kv4.3 potassium channel alpha subunit splice variants (Kv4.3L and Kv4.3S) that diverge only by a C-terminal, membrane-proximal, 19-residue stretch unique to Kv4.3L. Protein kinase C (PKC) phosphorylation of threonine 504 within the Kv4.3L-specific 19-residues mediates α-adrenergic inhibition of Ito in human heart. Kv4.3 is regulated in human heart by various β subunits, including cytosolic KChIP2b and transmembrane KCNEs, yet their impact on the functional effects of human Kv4.3 phosphorylation has not been reported. Here, this gap in knowledge was addressed using human Kv4.3 splice variants, T504 mutants, and human β subunits. Subunits were co-expressed in Xenopus laevis oocytes and analyzed by two-electrode voltage-clamp, using phorbol 12-myristate 13-acetate (PMA) to stimulate PKC. Unexpectedly, KChIP2b removed the inhibitory effect of PKC on Kv4.3L (but not Kv4.3L threonine phosphorylation by PKC per se), while co-expression with KCNE2, but not KCNE4, restored PKC-dependent inhibition of Kv4.3L-KChIP2b to quantitatively resemble previously reported effects of α-adrenergic modulation of human ventricular Ito. In addition, PKC accelerated recovery from inactivation of Kv4.3L-KChIP2b channels and, interestingly, of both Kv4.3L and Kv4.3S alone. Thus, β subunits regulate the response of human Kv4.3 to PKC phosphorylation and provide a potential mechanism for modifying the response of Ito to α-adrenergic regulation in vivo.